Case report: Autoimmune encephalitis associated with anti-CASPR2 antibody mimicking cerebral infarction - Chen, Ziqi; Tang, Jing (Frontiers in Immunology, 2023)
Autoimmune encephalitis associated with antibody against contactin-associated protein-like 2 (CASPR2) varies in its clinical presentation. The disease is difficult to distinguish from some other conditions without testing for anti-CASPR2 antibody in blood serum or cerebrospinal fluid. Cerebral lesions are typically detected by magnetic resonance imaging (MRI) in the medial temporal lobe or hippocampus. Here, we describe a patient with anti-CASPR2 antibody autoimmune encephalitis whose imaging manifestations mimicked infarction in the left frontal lobe. The 48-year-old man reported memory loss, convulsions, and disturbed consciousness one day after drinking wine. The right upper arm showed reduced autonomous movement after painful stimuli, and MRI showed abnormal hyperintensities in the left frontal lobe on T2 and fluid-attenuated inversion recovery sequences, restricted diffusion, and decreased cerebral blood flow, mimicking acute cerebral infarction. Contrast-enhanced T1-weighted MRI showed gyral enhancement involving the cortex and subcortical white matter. Computed tomography angiography did not identify culprit blood vessels. Symptoms did not improve with anti-platelet or lipid-lowering therapy. Screening for serum antibodies associated with autoimmune encephalitis detected antibody against CASPR2, and intravenous immunoglobulin therapy substantially improved symptoms. This case provides the first indication that anti-CASPR2 antibody-associated autoimmune encephalitis can manifest as involvement of the cortex and subcortical white matter in the frontal lobe based on MRI. It emphasizes the need for thorough investigation, including analysis of potential autoimmunity, of patients whose imaging findings mimic ischemic infarction.